(untitled) (GEOMATE Journal, 2017)
Analysis of Dobsonfly (a kind of Megaloptera, Protohermes grandis) larvae for concentrations of Cu and Zn was found to be an effective method of determining levels of Cu and Zn contamination of rivers in metal mine areas and non-metal mine catchments. Metal concentration in Dobsonfly larvae was used as an index of metal contamination because the amount of metal concentration in Dobsonfly larvae decreased with the dry weight of the larvae and also on the degree of metal present in the river water. Dobsonfly makes an excellent tool for contamination evaluation because of their easy classification, wide distribution and commonness. Furthermore, due to their relatively lengthy 2-3 year lifespan, river contamination assessment over a long term could be performed. In this study, Cu, Zn and As concentrations in river insect larvae in metal mine areas were found to be higher than those in non-mine catchments.